الرحلة بمنطقة توات اتجاهاتها و أغراضها: The trip to the Touat region, its directions and purposes - د. عبدالله كرّوم (Al Manhal Research Journal, 2023)
The Touat region (the state of Adrar in the southwest of Algeria) is of great importance, as it is an ancient scientific metropolis, and a transit route for commercial convoys between the north and south of the African continent. This region was also distinguished by its Qur’anic schools and Sufi angles, and its economic, cultural and symbolic presence, which made it a pilgrimage site for travelers, scholars, merchants and discoverers. It was visited by many of the famous travellers, such as Ibn Battuta, Al-Hasan Al-Wazzan, and Al-Ayashi, and they talked about it on their famous trips. In view of the strategic location of the Touat region, it interacted with the migrations of scholars and poets who migrated to it, and influenced and affected them. The Touat not only received delegations, but also engaged in discovery and research through the journey, and their trips varied in direction and purpose. Some of them traveled within the Algerian country, and some traveled towards Abroad, especially neighboring countries, and some of them headed towards the Holy Land to perform the rituals of Hajj, What is travel literature? How did it arise and develop? What are the most prominent twin trips? What directions did they take? And what are their purposes?